EFEKTIVITAS STRATEGI PEMBELAJARAN INTERAKTIF TERHADAP PENINGKATAN HASIL BELAJAR IPA PADA SISWA SEKOLAH DASAR - Yori Resvania; M. Suwignyo Prayogo; Shofiyatus Zakiyyah; Salisatul Mu’awanah (EDUCATOR : Jurnal Inovasi Tenaga Pendidik dan Kependidikan, 2025)
ABSTRACT Science learning in elementary schools ideally provides students with opportunities to explore natural phenomena directly so that scientific concepts can be understood meaningfully. However, classroom practices are still largely dominated by teacher-centered approaches, resulting in limited student engagement in scientific processes and suboptimal development of scientific literacy. This study aims to analyze the effectiveness of interactive learning as a strategy to improve the quality of science learning, particularly in terms of conceptual understanding, science process skills, learning motivation, and scientific literacy among elementary school students. The study employed a systematic review of national literature published between 2015 and 2025 by selecting articles that reported the implementation of interactive learning and its impact on science learning outcomes at the elementary level. Content analysis was conducted to identify types of interventions, variables examined, and the consistency of findings across studies. The results indicate that interactive learning through simple experiments, scientific discussions, interactive multimedia, and augmented reality technologies consistently enhances student engagement, strengthens conceptual understanding, and develops scientific skills and literacy. Therefore, interactive learning is considered relevant to the demands of 21st-century education and competency-based assessments and can be adopted as an effective strategy for teachers to improve the quality of science education in elementary schools. ABSTRAK Pembelajaran IPA di sekolah dasar idealnya memberi kesempatan kepada siswa untuk mengeksplorasi fenomena alam secara langsung agar konsep sains dipahami secara bermakna. Namun, praktik pembelajaran di kelas masih banyak didominasi pendekatan satu arah, sehingga keterlibatan siswa dalam proses ilmiah dan capaian literasi sains belum berkembang secara optimal. Kajian ini bertujuan menganalisis efektivitas pembelajaran interaktif sebagai strategi peningkatan kualitas pembelajaran IPA, khususnya dalam aspek pemahaman konsep, keterampilan proses sains, motivasi belajar, dan literasi sains siswa sekolah dasar. Penelitian ini menggunakan metode telaah sistematis terhadap literatur nasional yang terbit pada rentang tahun 2015–2025 dengan menyeleksi artikel yang melaporkan implementasi pembelajaran interaktif dan dampaknya terhadap hasil belajar IPA. Analisis isi dilakukan untuk mengidentifikasi bentuk intervensi, variabel yang dikaji, serta konsistensi temuan antarstudi. Hasil kajian menunjukkan bahwa pembelajaran interaktif melalui eksperimen sederhana, diskusi ilmiah, multimedia interaktif, dan teknologi augmented reality secara konsisten meningkatkan keterlibatan siswa, memperkuat pemahaman konsep, serta mengembangkan keterampilan ilmiah dan literasi sains. Dengan demikian, pembelajaran interaktif dinilai relevan dengan tuntutan pembelajaran abad ke-21 dan asesmen berbasis kompetensi, serta dapat dijadikan strategi efektif bagi guru dalam meningkatkan mutu pembelajaran IPA di sekolah dasar.